Decreased rhizodeposition, but increased microbial carbon stabilization with soil depth down to 3.6 m. (November 2020) - Peixoto, Leanne; Elsgaard, Lars; Rasmussen, Jim; Kuzyakov, Yakov; Banfield, Callum C.; Dippold, Michaela A.; Olesen, Jørgen E.
Abstract: Despite the importance of subsoil carbon (C) deposition by deep-rooted crops in mitigating climate change and maintaining soil health, the quantification of root C input and its microbial utilization and stabilization below 1 m depth remains unexplored. We studied C input by three perennial deep-rooted plants (lucerne, kernza, and rosinweed) grown in a unique 4-m deep RootTower facility. 13 C multiple pulse labeling was applied to trace C flows in roots, rhizodeposition, and soil as well as 13 C incorporation into microbial groups by phospholipid fatty acids and the long-term stabilization of microbial residues by amino sugars. The ratio of rhizodeposited 13 C in the PLFA and amino sugar pools was used to compare the relative microbial stability of rhizodeposited C across depths and plant species. Belowground C allocation between roots, rhizodeposits, and living and dead microorganisms indicated depth dependent plant investment. Rhizodeposition as a fraction of the total belowground C input declined from the topsoil (0–25 cm) to the deepest layer (360 cm), i.e., from 35%, 45%, and 36%–8.0%, 2.5%, and 2.7% for lucerne, kernza, and rosinweed, respectively, where lucerne had greater C input than the other species between 340 and 360 cm. The relative microbial stabilization of rhizodeposits in the subsoil across all species showed a dominance of recently assimilated C in microbial necromass, thus indicating a higher microbial stabilization of rhizodeposited C with depth. In conclusion, we traced photosynthates down to 3.6 m soil depth and showed that even relatively small C amounts allocated to deep soil layers will become microbially stabilized. Thus, deep-rooted crops, in particular lucerne are important for stabilization and storage of C over long time scales in deep soil. Graphical abstract: Image 1 Highlights: Rhizodeposition strongly declined with depth across all plant species. Microbial stabilization of rhizodeposits increases with depth. Deep-rooted crops are important for storage and stabilization of rhizodeposition.